Styles of aqueous alteration on Mars - Cloutis, Edward A (The American mineralogist, 2016)
While phyllosilicates were the first water-bearing minerals inferred to be present on Mars from analysis of Earth-based telescopic spectra (McCord et al. 1982), it took recent spacecraft missions to enable mapping the global distribution and determining the types of specific species that are present on the surface and their geological context.